Risk of congenital anomalies in the vicinity of municipal solid waste incinerators. Issue 1 (22nd December 2003) - Cordier, S; Chevrier, C; Robert-Gnansia, E; Lorente, C; Brula, P; Hours, M
Abstract : Background: Although municipal solid waste incineration (MSWI) has contributed to increase the overall environmental load of particulate matter containing dioxins and metals, evidence of health consequences to populations is sparse. Aims: To assess at a regional level (in southeast France) the impact of these emissions on birth defect rates. Methods: Communities with fewer than 50 000 inhabitants surrounding the 70 incinerators that operated at least one year from 1988 to 1997 were studied. Each exposed community (n = 194) was assigned an exposure index estimated from a Gaussian plume model. Poisson models and a reference population of the 2678 unexposed communities in the region were used to calculate relative risks for congenital malformations, adjusted for year of birth, maternal age, department of birth, population density, average family income, and when available, local road traffic. Results: The rate of congenital anomalies was not significantly higher in exposed compared with unexposed communities. Some subgroups of major anomalies, specifically facial clefts and renal dysplasia, were more frequent in the exposed communities. Among exposed communities, a dose-response trend of risk with increasing exposure was observed for obstructive uropathies. Risks of cardiac anomalies, obstructive uropathies, and skin anomalies increased linearly with road traffic density. Conclusions: Although both incinerator emissions and road traffic may plausibly explain some of the excess risks observed, several alternative explanations, including exposure misclassification, ascertainment bias, and residual confounding cannot be excluded. Some of the effects observed, if real, might be attributable to old-technology MSWIs and the persistent pollution they have generated.